High resolution mapping of strains and rotations using electron backscatter diffraction - Wilkinson, A; Meaden, G; Dingley, D (Taylor and Francis, 2013)
The angular resolution of electron backscatter diffraction (EBSD) measurements can be significantly improved using an analysis based on determination of small shifts in features from one pattern to the next using cross-correlation functions. Using pattern shift measurements at many regions of the pattern, errors in the best fit strain and rotation tensors can be reduced. The authors show that elements of the strain tensor and small misorientations can be measured to ± 10−4 and ±0·006° for rotations. We apply the technique to two quite different materials systems. First, we determine the elastic strain distribution near the interface in a cross-sectioned SiGe epilayer, Si substrate semiconductor heterostructure. The plane stress boundary conditions at the sample surface are used to separate every term in the strain tensor. Second, the applicability to structural materials is illustrated by determining the lattice curvature caused by dislocations within the plastic zone associated with the wake and tip of a fatigue crack in a Ni based superalloy. The lattice curvatures are used to calculate the geometrically necessary dislocation content in the plastic zone.